2019
DOI: 10.2519/jospt.2019.8590
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Decreased Scapulothoracic Upward Rotation on Subacromial Proximities

Abstract: BACKGROUND: Decreased scapulothoracic upward rotation has been theorized to increase an individual's risk for rotator cuff compression by reducing the clearance for the tendons in the subacromial space (ie, subacromial proximities). However, the impact of decreased scapulothoracic upward rotation on subacromial proximities has not been tested during dynamic in vivo shoulder motion. OBJECTIVE:To determine the impact of decreased scapulothoracic upward rotation on subacromial proximities. METHODS:Shoulder kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…Initial work by Thomas et al 35 suggested acromiohumeral distance (measured via ultrasound) was not significantly correlated with scapular upward rotation angular position when the arm was at the side or at 90 • humerothoracic elevation in asymptomatic college baseball players. Recent work, 37 however, suggests the relationship between scapulothoracic upward rotation and subacromial proximities is not absolute, but depends on the angle of humerothoracic elevation. The study quantified shoulder kinematics and minimum distance (normalized to the rotator cuff tendon thickness) in 40 symptomatic and asymptomatic individuals during dynamic scapular plane abduction.…”
Section: Scapulothoracic Kinematicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial work by Thomas et al 35 suggested acromiohumeral distance (measured via ultrasound) was not significantly correlated with scapular upward rotation angular position when the arm was at the side or at 90 • humerothoracic elevation in asymptomatic college baseball players. Recent work, 37 however, suggests the relationship between scapulothoracic upward rotation and subacromial proximities is not absolute, but depends on the angle of humerothoracic elevation. The study quantified shoulder kinematics and minimum distance (normalized to the rotator cuff tendon thickness) in 40 symptomatic and asymptomatic individuals during dynamic scapular plane abduction.…”
Section: Scapulothoracic Kinematicsmentioning
confidence: 99%
“…Three-dimensional methods used to quantify subacromial proximities include kinematic tracking and modeling using either single- 37 or bi-plane radiography, 7,38,39 stereophotogrammetry, 28 3D image reconstruction, 40 or computational modeling. 41,42 Although these 3D approaches provide higher accuracy, they often require custom equipment and data processing algorithms, and significant data processing time, which hinder broad use, clinical translation, and large sample sizes.…”
Section: Imaging Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other Authors reported a range of apparently contrasting results concerning the increment or decrement of scapular rotations in various athletes populations (Su et al, 2004;Ebaugh et al, 2006;Maenhout et al, 2015). Discrepancies between studies can be attributed to the degree of humeral elevation and the postural arrangement adopted in the fatigue protocols (prone, sitting or standing position), the applied load (bottle, elastic band, and sport-specific actions) or upper limb movement (elevation or abduction) (Lawrence et al, 2019).…”
Section: Introductionmentioning
confidence: 99%